Integrating Islamic Values ​​and Science to Develop Students with Noble Morals - Ratu Suntiah; Mursidin; Hani Yuliawati; Habibah Nur Azizah; Siti Wifa Uswatussolihah (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to explore the integration of Islamic values and science in the education system and its impact on the formation of noble students. . Methods This research is a qualitative research with a literature study approach. The data used in this research is in the form of document data, both from textbooks, scientific journals, and other relevant document sources. The results showed that teachers play an important role as role models and facilitators in instilling the principles of integration. Overall, this integration helps students develop into balanced individuals, possessing intelligence and moral goodness, and ready to contribute positively in society.